Contribution of the Twin-Arginine Translocation System to the Intracellular Survival of Salmonella Typhimurium in Dictyostelium discoideum - Urrutia, Ítalo M.; Sabag, Andrea; Valenzuela, Camila; Labra, Bayron; Álvarez, Sergio A.; Santiviago, Carlos A. (Frontiers in Microbiology, 2018)
The twin-arginine translocation (Tat) system is a specialized secretion pathway required for bacteria to export fully folded proteins through the cytoplasmic membrane. This system is crucial during Salmonella infection of animal hosts. In this study, we show that S. Typhimurium requires the Tat system to survive and proliferate intracellularly in the social amoeba D. discoideum. To achieve this, we developed a new infection assay to assess intracellular bacterial loads in amoebae by direct enumeration of colony forming units (CFU) at different times of infection. Using this assay we observed that a ΔtatABC mutant was internalized in higher numbers than the wild type, and was defective for intracellular survival in the amoeba at all times post infection evaluated. In addition, we assessed the effect of the ΔtatABC mutant in the social development of D. discoideum. In contrast to the wild-type strain, we observed that the mutant was unable to delay the social development of the amoeba at 2 days of co-incubation. This phenotype correlated with defects in intracellular proliferation presented by the ΔtatABC mutant in D. discoideum after 24 h of infection. All phenotypes described for the mutant were reverted by the presence of a plasmid carrying tatABC genes, indicating that abrogation of Tat system attenuates S. Typhimurium in this model organism. Overall, our results indicate that the Tat system is crucial for S. Typhimurium to survive and proliferate intracellularly in D. discoideum and for virulence in this host. To the best of our knowledge, this is the first report on the relevance of the Tat system in the interaction of any bacterial pathogen with the social amoeba D. discoideum.